An Empirical Investigation of the Relationship Between Corporate Success and the Implementation of Agile Principles in the Manufacturing Industry in the GSA Region - Gronau, Christian (Digital Repository of Theses - SSBM Geneva, 2025)
The dissertation “An empirical investigation of the relationship between corporate success and the implementation of agile principles in the manufacturing industry in the GSA region” investigates the relationship between business success and the introduction of agile principles in the manufacturing industry in Germany, Switzerland and Austria (GSA region). The aim of this work is to capture the impact of agile principles on business success in the manufacturing industry, to provide practical insights for decisionmakers, and to deliver scientific input. The need for this research stems from the fact that, despite its widespread use, agility has not yet been investigated in depth in relation to the manufacturing industry in the GSA region. Based on this, the following research questions were defined: which agile principles are most effective? How does the introduction of agile principles influence company metrics such as time-to-market, product quality or cost efficiency? Furthermore, what best practices already exist? The methodology of the work is based on a mixed-method approach. Quantitative data were collected through an expert survey in which employees and managers were asked about agile principles, their introduction and their effects. In order to gain further insights into the experience of practitioners, the analysis was supplemented by two expert-interviews. The results of the research show that agile principles such as continuous improvement, self-organising teams and collaborative working have a positive influence on efficiency, product quality, time-to-market and employee satisfaction. It should also be emphasised that clear management support, targeted training and a cultural change within the company are decisive factors for success. Barriers were also identified, such as technological limitations and silo-like structures. In summary, the study concludes that the introduction of agile principles in the manufacturing industry in the GSA region is not only possible but also sensible, if it is individually adapted, strategically supported and culturally anchored. The work thus provides scientifically grounded insights into the effectiveness of agile approaches in a traditionally structured industry and contributes to improving the manageability of agile transformations in practice.